Factors affecting agent banking adoption by selected communities in Selangor, Malaysia - Shahrizan Adzham, Ahmad (2021)
Agent banking was introduced by Bank Negara Malaysia (BNM) to deliver banking services outside the bank branches using retail agents, such as sundry shops, post offices and petrol stations, among others. Through agent banking, the previously unserved and underserved customers now have easy access to a financial institution near them without having to travel a long distance to a bank branch. Nevertheless, several challenges still exist, particularly among the poor and rural segments in accepting this new way of banking. This study aims to examine the impact of attitude, subjective norm, perceived behavior control, perceived usefulness, perceived ease of use, perceived risk, and perceived security on the actual use of agent banking. This study employs the technology acceptance model (TAM) and the theory of planned behavior (TPB) as the guiding principle. Data collected from 247 agent bank users in Selangor was analysed via the partial least squares-structural equation modelling approach. The results revealed that attitude, perceived behavioural control, perceived usefulness, and perceived risk were significant antecedents of the actual use of agent banking. The empirical results furnish vital insights to the financial institutions in formulating their network expansion strategies to increase customer base in untapped areas, and to BNM in developing policies to strengthen the financial inclusion agenda. This study can be a reference point to the government in developing socio-economic plans to improve the financial well-being of the publics.